Seeking support: insights into women’s mental health help-seeking behavior in Bangladesh - Walter, Hannah; Craig, Maggie E.; Ali, Masum; Faruque, Shahriar; Saha, Sanjib (Frontiers in Global Women's Health, 2025)
IntroductionDepression and anxiety are leading contributors to the global burden of disease among women yet help-seeking for mental health concerns remains limited in lower-middle-income countries. This study aimed to estimate the prevalence of anxiety, depression, and help-seeking behaviors, and to identify factors associated with the absence of help-seeking among ever-married women of reproductive age in Bangladesh.MethodsWe conducted a cross-sectional analysis using nationally representative data from the 2022 Bangladesh Demographic and Health Survey. Mental health outcomes were assessed using the Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9 screening tools. Help-seeking behavior was defined as any attempt to obtain external support for mental health concerns. Multivariable logistic regression models, accounting for survey design and sampling weights, were used to examine predictors of not seeking help following Behavioral Model of Health Services Use by Andersen and Davidson.ResultsAmong 19,987 women aged 15–49 years, 5.1% reported depression, 19.7% reported anxiety, and 20.4% had either condition. Only 20.5% of those with anxiety or depression reported help-seeking, predominantly from informal sources such as family and neighbors. Rural residence, older age, and a professional diagnosis of anxiety were associated with increased help-seeking, while low health autonomy and residence in the Barishal division were linked to lower help-seeking. Formal help-seeking was rare, and significant regional disparities were observed. One in five ever-married women of reproductive age in Bangladesh experiences anxiety or depression, but help-seeking remains low, especially for formal services.DiscussionInformal networks play a critical role in support. Interventions should address contextual and individual barriers, strengthen social support, and improve access to mental health care, particularly in underserved regions.